2019
DOI: 10.1891/1061-3749.27.3.e153
|View full text |Cite
|
Sign up to set email alerts
|

An Arabic Translation, Reliability, Validity, and Feasibility of the Richards–Campbell Sleep Questionnaire for Sleep Quality Assessment in ICU: Prospective-Repeated Assessments

Abstract: Background and PurposeTo translate Richards–Campbell Sleep Questionnaire (RCSQ) into the Arabic language (RCSQ-A), to assess content validity of the translated tool, to analyze the internal consistency, and to evaluate its feasibility.MethodsA rigorous translation was completed using the process of translation by World Health Organization. Cognitive debriefing interviews were performed. Repeated assessments using RCSQ-A was conducted in critical care patients in Saudi Arabia.ResultCronbach's alpha of .89 was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The RCSQ has demonstrated content validity, criterion validity against PSG, and internal consistency reliability with Cronbach's alpha of 0.90 ( 2 ), and has been used in well over 1,000 ICU patients. The RCSQ has been translated and validated in other languages, including versions in Arabic ( 82 ), Chinese ( 83 ), German ( 84 ), Japanese ( 85 ), and Portuguese ( 86 ). Although the RCSQ was developed as a self-assessment tool, some studies explored its patient-nurse interrater agreement.…”
Section: Resultsmentioning
confidence: 99%
“…The RCSQ has demonstrated content validity, criterion validity against PSG, and internal consistency reliability with Cronbach's alpha of 0.90 ( 2 ), and has been used in well over 1,000 ICU patients. The RCSQ has been translated and validated in other languages, including versions in Arabic ( 82 ), Chinese ( 83 ), German ( 84 ), Japanese ( 85 ), and Portuguese ( 86 ). Although the RCSQ was developed as a self-assessment tool, some studies explored its patient-nurse interrater agreement.…”
Section: Resultsmentioning
confidence: 99%
“…The Arabic version of RCSQ (RCSQ-A)15 and the modified Sleep in Intensive Care Questionnaire (SICQ)16 were administered each morning between 07:00 and 12:00 hours until the day the patient was due to be discharged from the ICU. Details of study instruments can be found in online supplementary material 1.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of translated RCSQ was investigated by test‐retest reliability with two sets of different questionnaires in 2‐hour interval. The test‐retest reliability of Thai version of RCSQ (T‐RCSQ) was excellent, as supported by high intra‐class correlation coefficients and high internal consistency (Cronbach's alpha .964), which was comparable to that of the original English version of RCSQ scale and to those of other international versions 10,11,22‐25 …”
Section: Discussionmentioning
confidence: 82%